2011
DOI: 10.1177/1557988311408410
|View full text |Cite
|
Sign up to set email alerts
|

Suicide From the Perspectives of Older Men Who Experience Depression

Abstract: Depression can be a pathway to older men's suicide, yet the mechanisms by which this can occur are poorly understood. A qualitative study of 22 older men who self-identified or were formally diagnosed with depression was conducted to describe the connections between masculinity, depression, and suicide. Analyses of individual interviews revealed that cumulative losses around social bonds were central to older men's depression, apathy for living, and thoughts about suicide. Prominent were men's self-assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 49 publications
2
47
1
3
Order By: Relevance
“…Consistent and repeated findings about suicide in elderly confirms that suicide rates are higher in males than females 38 . Overall, research put forward men's' alignment to masculine ideals influencing both the connectedness and detachment between older men's depression and suicide 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent and repeated findings about suicide in elderly confirms that suicide rates are higher in males than females 38 . Overall, research put forward men's' alignment to masculine ideals influencing both the connectedness and detachment between older men's depression and suicide 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Research also indicates that Canadian men are less likely to report intentions to seek professional help for mental health problems, perhaps because they have less positive attitudes toward treatment seeking than women (Mackenzie et al, 2006). An Australian study highlighted the need to address barriers to help-seeking in males with severe mental illness disorders (Harris et al, 2015), a recommendation echoed in a European Union study (Kovess-Masfety et al, 2014 help-seeking and self-management of depression and/or suicide prevention (Oliffe et al, 2011a. Common to this emergent work is the centrality of mental health literacy, and its operationalization toward advancing men's helpseeking and informing gender-specific and sensitive services to better address male depression and suicide.…”
Section: Men's Depression and Suicide And Mental Health Literacymentioning
confidence: 99%
“…Similarly, some research has shown that depression may present an opportunity to rethink and reconstruct masculinities along alternative but progressive lines where, for example, emotional communication is valued (e.g. Oliffe et al, 2011). A few studies have indicated that some men appreciate the emotional support offered by partners, family and peers (Ramirez & Badger, 2014), including fellow depression sufferers, who can help to normalise the situation (Cutcliffe et al, 2013).…”
mentioning
confidence: 99%